2009
DOI: 10.1021/la9030969
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Mechanics of Peptide Nanofiber Gels

Abstract: The mechanical properties of self-assembled fibrillar networks are influenced by the specific intermolecular interactions that modulate fiber entanglements. We investigate how changing these interactions influences the mechanics of self-assembled nanofiber gels composed of peptide amphiphile (PA) molecules. PAs developed in our laboratory self-assemble into gels of nanofibers after neutralization or salt-mediated screening of the charged residues in their peptide segment. We report here on the gelation, stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
205
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(224 citation statements)
references
References 41 publications
18
205
0
1
Order By: Relevance
“…Comparing IDIDI (1 wt %) and D2I3 (2 wt %) hydrogels, the G′ value increased by two orders of magnitude from 2 to 200 kPa, respectively. These stiffness values are in the region of many soft tissues and compare well to previously published peptide hydrogel systems, including aromatic peptides4, 17 and peptide–amphiphile hydrogels 27, 28. The ability to tune the G′ value across a large range holds great promise for applications in tissue engineering, given that the behavior of cells has been found to be heavily influenced by the mechanical properties of their surrounding environment 29, 30…”
supporting
confidence: 79%
“…Comparing IDIDI (1 wt %) and D2I3 (2 wt %) hydrogels, the G′ value increased by two orders of magnitude from 2 to 200 kPa, respectively. These stiffness values are in the region of many soft tissues and compare well to previously published peptide hydrogel systems, including aromatic peptides4, 17 and peptide–amphiphile hydrogels 27, 28. The ability to tune the G′ value across a large range holds great promise for applications in tissue engineering, given that the behavior of cells has been found to be heavily influenced by the mechanical properties of their surrounding environment 29, 30…”
supporting
confidence: 79%
“…However, it is clear that similar observations can be found with other examples. Greenfield et al 92 have shown that gels with different properties can be formed from the same peptide amphiphile. As with the 2NapFF above, these can be gelled by the addition of a calcium salt to a solution of the LMWG in water or by the addition of acid.…”
Section: Process Of Assemblymentioning
confidence: 99%
“…59 The mechanical properties of the gels can be controlled by the structure and concentration of PAs; however, the ability to control mechanical properties by modifying the interactions between fibers has also been demonstrated. 60 Pore structure and cellular infiltration Control of pore structure is an important aspect of scaffold fabrication, as it directly affects cell infiltration. Of the three production methods discussed, phase separation allows for the greatest control of pore structure.…”
Section: 54mentioning
confidence: 99%